Determination of Levetiracetam in Human Plasma by Dispersive Liquid-Liquid Microextraction Followed by Gas Chromatography-Mass Spectrometry - Greyce Kelly Steinhorst Alcantara; Leandro Augusto Calixto; Luiz Alberto Beraldo de Moraes; Regina Helena Costa Queiroz; Anderson Rodrigo Moraes de Oliveira; Cristiane Masetto de Gaitani (Journal of Analytical Methods in Chemistry)
Levetiracetam (LEV) is an antiepileptic drug that is clinically effective in generalized and partial epilepsy syndromes. The use of this drug has been increasing in clinical practice and intra- or -interindividual variability has been exhibited for special population. For this reason, bioanalytical methods are required for drug monitoring in biological matrices. So this work presents a dispersive liquid-liquid microextraction method followed by gas chromatography-mass spectrometry (DLLME-GC-MS) for LEV quantification in human plasma. However, due to the matrix complexity a previous purification step is required. Unlike other pretreatment techniques presented in the literature, for the first time, a procedure employing ultrafiltration tubes Amicon® (10 kDa porous size) without organic solvent consumption was developed. GC-MS analyses were carried out using a linear temperature program, capillary fused silica column, and helium as the carrier gas. DLLME optimized parameters were type and volume of extraction and dispersing solvents, salt addition, and vortex agitation time. Under chosen parameters (extraction solvent: chloroform, 130 μL; dispersing solvent: isopropyl alcohol, 400 μL; no salt addition and no vortex agitation time), the method was completely validated and all parameters were in agreement with the literature recommendations. LEV was quantified in patient’s plasma sample using less than 550 μL of organic solvent.